2023
DOI: 10.3389/fpsyg.2023.1081086
|View full text |Cite
|
Sign up to set email alerts
|

How and why humans trust: A meta-analysis and elaborated model

Abstract: Trust exerts an impact on essentially all forms of social relationships. It affects individuals in deciding whether and how they will or will not interact with other people. Equally, trust also influences the stance of entire nations in their mutual dealings. In consequence, understanding the factors that influence the decision to trust, or not to trust, is crucial to the full spectrum of social dealings. Here, we report the most comprehensive extant meta-analysis of experimental findings relating to such huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 115 publications
0
1
0
Order By: Relevance
“…Attitudes toward others are one of the most researched constructs in the social sciences [75][76][77][78][79][80]. Extensive research demonstrated the effects of positive attitudes toward others [81,82] as well as the effects of negative ones [83][84][85].…”
Section: Attitudes Toward Peoplementioning
confidence: 99%
“…Attitudes toward others are one of the most researched constructs in the social sciences [75][76][77][78][79][80]. Extensive research demonstrated the effects of positive attitudes toward others [81,82] as well as the effects of negative ones [83][84][85].…”
Section: Attitudes Toward Peoplementioning
confidence: 99%